An Analysis of Teacher’s Gestures in Facilitating Students’ Vocabulary Mastery at SMPN 1 Rejang Lebong (A Mixed Methods Sequential Explanatory Research Design) - Sari, Suci Permata; Prihantoro, Prihantoro; Utami, Henny Septia (ICONELT, 2024)
The gestures used by teachers are crucial for both educators and learners, as they aid in better understanding spoken language. This research aims to elucidate teacher gestures’ influence and identify the specific gestures used in vocabulary instruction. This mixed-methods research utilized observation, with note-taking and video recording as data collection techniques. The object of this research was first-grade students of SMPN 1 Rejang Lebong, which consisted of 34 students. The data were taken from the results of tests, questionnaires, interviews, and observations and analyzed with simple regression analysis in SPSS. The results of the analysis and discussion of this research showed a significant influence of teacher’s gestures on students’ vocabulary mastery. It is concluded that 84.8% of teacher gestures can facilitate students’ vocabulary mastery, and 77% of teacher gestures can support verbal communication, reduce the ambiguity of language, and increase understanding of the concept. Additionally, five types of gestures were found in this study. It is facial expression, posture, gestures, touch, and eye contact. The results of all kinds of gestures are 20 gesture items. Facial expressions 6 items, posture 3 items, gesture 5 items, touch 2 items and eye contact 4 items.